Analysis of Mango Farming in Critical Land in Denanyar Village, Jombang - Dhini Romadoni; Zulfikar; Rohmat Hidayat (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
This study aims to determine: 1) the characteristics of mango farmers on critical land in Desa Denanyar Jombang 2) the feasibility of mango farming in the critical land of Denanyar Village in terms of R/ C ratio. The method used is a simple random sample. A total sample of 30 domestic actors Homemade mango. The results of the analysis show that: 1) Mango farming carried out mango farmers are not the main source of income. Usatan actors consisting of various ages and occupations use the yard as an additional source of income.2)The amount of R/ C in mango farming in Deanayar Village, Jombang District, Jombang Regency is 4.26. For every expense of Rp. 1.00, the mango farmers will receive an income of Rp. 4.26 so that they get a profit of Rp. 3.26. With Thus, mango farming in the critical land of Denanyar Village is profitable to cultivate.